Succession of a foreign national resident in a foral law territory: the skipped issues. Judgment of the Court of Appeal of Girona number 367/2019 of 4th October - Carrillo Pozo, Luis F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
In the case of a testamentary succession of a British, a court must carry out an activity aimed basically at the elucidation of three issues: Regardless of the habitual residence of the deceased, where had he his domicile? Do the testamentary dispositions have the value of choice of law?; once the renvoi it’s accepted, can the Law of the Autonomous Community be applied without further ado, based on a purely territorial criterion? In the case analyzed –being the regulation 650/2012 inapplicable-, the Provincial Court skips out these analysis. But if the regulation had been applicable, the result could have been very different.